Visual naming speed and its relation to the components of reading in children with reading disability - Lopa, Maria Raquel (Ann Arbor Michigan Bell & Howell Information and Learning Company, 2000)
The study examined performance on measures of naming speed (i.e., rapid naming of words, colors, and pictures) and the relative contribution of naming speed to phonological decoding, word identification, and reading comprehension in children with reading disability. Forty children with reading disability (mean age = 10 years, 7 months) were compared with a control group of 44 normally achieving readers of the same chronological age (mean age = 10 years, 8 months) and a control group of 42 normally achieving readers of the same oral word reading level (mean age = 8 years, 8 months). Repeated measures analysis of variance demonstrated that the children with reading disability performed more poorly than the chronological age control group on the rapid naming measures. The performance of the children with reading disability was not significantly different from the performance of the reading-level control group. Multiple regression analyses indicated that there were group differences in the contribution of naming speed to the components of reading. After controlling for Deviation IQ, naming speed contributed to the variance on phonological decoding and word identification only for the children with reading disability. For the three groups, naming speed did not account for a significant amount of variance on reading comprehension after Deviation IQ was partialled out of the regression equation. The results of the study suggest that at age 10 years, children with reading disability continue to perform below age-appropriate levels on measures of rapid naming. Their performance is similar to younger children reading at the same reading level. The results also indicate the differential importance of naming speed to the components of reading. Among children with reading disability, slow naming speed continues to have an impact on lower-level reading components (i.e., phonological decoding and word identification).--Abstract.
Thesis (Ph.D.)--Fordham University, 2000.
Keywords: Reading disability; Children with disabilities